Enhanced extractive fermentation for propionic acid production using propioni bacterium acidipropionici immobilized in fibrous red bioreactor and hollow fiber membrane extractors - De Guzman, Lucita
Usingtraditional fermentation and extraction,propionic acid production was studied with the aim of developing an enhanced extractive fermentation process using propionibacterium acidipropionici (ATCC 4875). Three experimental phases were conducted.